EPICARDIAL MONO- AND BIVENTRICULAR ELECTROCARDIOSTIMULATION IN TREATMENT OF CONDUCTION DISORDERS IN NORMAL SYSTOLIC FUNCTION - An. M. Osadchiy; A. V. Kamenev; S. V. Karuzin; S. G. Shcherbak; D. S. Lebedev (Российский кардиологический журнал, 2015)
Aim. To reveal the specifics, and to evaluate the efficacy of implantation of epicardial (myocardial) electrodes under the conditions of artificial circulation and to define their influence on electromechanical parameters of the heart including pumping function.Material and methods. The results were analyzed of intraoperation and short-term (up to 24 months) results of implantation of epicardial electrodes under the conditions of AC in 32 patients, operated in 2007-2014 yy. For 32 patients the electrode was implanted (fixated) epicardially under the conditions of AC for conduction disorder correction after the main stage of cardiosurgical intervention. Including the fixation of epicardial electrode to both ventricles (group A, n=23) was done as biventricular ECS, and to one ventricle (group B, n=9) — monoventricular ECS. The following investigations were done: clinical examination, ECG, 6-minute walking test (6-WT), Echocardiography with dyssynchrony evaluation in M-, B-, doppler and tissue regimens, programming of ECS.Results. Mean follow-up period in both groups was 17±1,9 months. In 23 patients fixation of “-”-pole of epicardial electrode was done on the lateral surface of the left ventricle, and “+”-pole on posterior surface of the right ventricle, and in 8 patients epicardial electrode “+” and “-” was fixated in the area of lateral surface of the left ventricle and in one — area of the right ventricle if possible to the basal part. In 7 patients the atrial epicardial electrode was fixed to the base of the right atrium. So, we reached in 11 cases the 3-chamber ECS (CPT-ECS), in 12 — “biventricular” ECS (patients with permanent AF) and in 9 — monoventricular cardiostimulation.Conclusion. Epicardial (myocardial) biventricular stimulation of the heart is efficient method of rhythm disorder correction and the method of choice in those who need the replacement of endocardial ECS system, in heart defects patients, and if with CHF. While implanting epicardial systems there is a possibility to visually define the points and place of electrodes fixation. In biventricular ECS in dynamics there are significantly better results in the heart synchronicity parameters, that also was confirmed by the improvement of the LV systolic function and its remodeling in 12 months.